A comparative analysis of the temperature behavior and multiple tropopause events derived from GPS, radiosonde and reanalysis datasets over Argentina, as an example of Southern mid latitudes - Lakkis, Susan Gabriela (2009)
Fil: Lakkis, Susan Gabriela. Pontificia Universidad Católica Argentina. Facultad de Ciencias Agrarias. Equipo Interdisciplinario para el Estudio de Procesos Atmosféricos en el Cambio Global; Argentina